IMPROVING BUSINESS ENGLISH AND MANAGEMENT STUDENTS’ READING COMPREHENSION THROUGH STRUCTURAL ANALYSIS - Fariska Wulandari (Jurnal Pendidikan Bahasa, 2018)
This research was purposed to find out how the use of structural analysis improve the reading comprehension of E class second semester students of Business English and Management Major Tonggak Equator Polytechnic in the academic year 2017-2018 and how significant does the use of structural analysis improve the reading comprehension of E class second semester students of Business English and Management Major Tonggak Equator Polytechnic in academic year 2017-2018. This research was classroom action research which was set out in two cycles, they are the first and second cycle. The subject of this research was E class second semester students of Business English and Management Concentration of Tonggak Equator Polytechnic in the academic year 2017-2018. Field note and test were used in collecting the data. The test consists of pre-test and progress-test. The data of the students' pre-test and progress-test score were analyzed by using the mean score and the data of the observation by using field note was analyzed descriptively. The finding of the research was structural analysis positively improved the reading comprehension of E class second semester students of Business English and Management Major Tonggak Equator Polytechnic in academic year 2017-2018 within two cycles, and the significance of the use of structural analysis in improving the reading comprehension of E class second semester students of Business English and Management Major Tonggak Equator Polytechnic in academic year 2017-2018 could be seen based on the test given they were 64 for the pre-test, 71.6 for the first progress-test and 83.4 for the second progress-test, and from the field note, that the students looked tired, sleepy, looked for answer from student beside them and could not finish the test by the time given by the researcher in the first cycle but have significant progress in the second cycle that the students looked more relax in doing the test and could finish the test by the time given by the researcher.Keywords: reading comprehension, structural analysis, classroom action research.